Strategi Multitalenta untuk Mengaktifkan Siswa dalam Pembelajaran Menulis Naskah Drama - Masyithah Maghfirah Rizam; Kristanti Ayuanita; Hesty Kusumawati (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2021)
Language skills that are important and used in everyday life, one of which is writing skills. This writing skill is a form of active productive skill because the writer actively produces or expresses his ideas. This research is a descriptive qualitative research that aims to describe a multitalented strategy to activate students in learning to write drama scripts. Innovative strategies are needed in learning to write drama scripts so that students are encouraged to be active, critical, and creative students. Multitalented Strategy is a strategy in which each student mobilizes all his talents in writing drama scripts.